Phase 1 Evaluation of Elezanumab (Anti–Repulsive Guidance Molecule A Monoclonal Antibody) in Healthy and Multiple Sclerosis Participants. Issue 2 (30th November 2022) - Kalluri, Hari V.; Rosebraugh, Matthew R.; Misko, Thomas P.; Ziemann, Adam; Liu, Wei; Cree, Bruce A. C.
Abstract : Objective: This study was undertaken to describe the safety, tolerability, pharmacokinetics, and immunogenicity of elezanumab (ABT‐555), a fully human monoclonal antibody (mAb) directed against repulsive guidance molecule A (RGMa), in healthy and multiple sclerosis (MS) study participants. Methods: The single‐center, first‐in‐human, single ascending dose (SAD) study evaluated elezanumab (50–1, 600mg intravenous [IV] and 150mg subcutaneous) in 47 healthy men and women. The multicenter multiple ascending dose (MAD; NCT02601885) study evaluated elezanumab (150mg, 600mg, and 1, 800mg) in 20 adult men and women with MS, receiving either maintenance or no immunomodulatory treatment. Results: No pattern of study drug‐related adverse events was identified for either the SAD or MAD elezanumab regimens. Across both studies, the Tmax occurred within 4 hours of elezanumab IV infusion, and the harmonic mean of t 1/2 ranged between 18.6 and 67.7 days. Following multiple dosing, elezanumab Cmax, area under the curve, and Ctrough increased dose‐proportionally and resulted in dose‐dependent increases in elezanumab cerebrospinal fluid (CSF) concentrations. Elezanumab CSF penetration was 0.1% to 0.4% across both studies, with CSF levels of free RGMa decreased by >40%. Changes in CSF interleukin‐10 (IL‐10) and free RGMa demonstrated dose/exposure‐dependence. Interpretation: The elezanumab pharmacokinetic profile supports monthly, or bimonthly, administration of up to 1, 800mg with the option of a loading dose of 3, 600mg. Elezanumab partitioning into CSF is within the range expected for mAbs. Reduced CSF levels of free RGMa demonstrate central nervous system target binding of elezanumab with an apparent maximal effect at 1, 800mg IV. Exposure‐associated increases in CSF IL‐10, an anti‐inflammatory cytokine with neuroprotective/neurorestorative properties, support potential pathway modulation in MS participants. ANN NEUROL 2023;93:285–296